(untitled) (Journal of Nobel Medical College, 2017)
Background: Learning disability refers to a heterogeneous group of disorders manifested by difficulty in reading, writing, spelling and reasoning ability. It usually show up when a child has difficulty reading, speaking, writing, figuring out a math problem, communicating with parents or paying attention in class. Children with learning disability can succeed in school and can have successful career in life if right support and intervention is provided to them. Material & Methods: Quantitative approach with Descriptive crosssectional design was used to assess the knowledge of primary school teachers. A structured knowledge questionnaire was developed focusing on learning disabilities. The study was carried out in 16 schools of Dharan, Nepal. About 150 primary school teachers were selected by convenience sampling technique. Structured knowledge questionnaire was used to collect needed data on knowledge of primary school teachers. The data collected were tabulated and analyzed by using descriptive and inferential statistics. Results: Majority, 79 (52.67%) of the primary school teachers had moderately adequate knowledge and 71 (47.33%) had inadequate knowledge regarding learning disabilities. There was a significant association of knowledge of primary school teachers with demographic variables such as class involved in teaching. Conclusion: The school teachers have inadequate knowledge regarding learning disabilities. The teachers play an important role in identifying learning disabilities in school children at initial state. The children with learning difficulties should be helped at early stage and proper training and guidance should be provided to them. Journal of Nobel Medical College Volume 6, Number 1, Issue 10 (January-June, 2017), Page: